INNOVATIVE MARKETING COMMUNICATION PRODUCTS OF GRAMEEN SHARIA BANKING - Kartika Marella Vanni (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
The Grameen Bank is a financing model to provide capital from banks to economically disadvantaged communities. Islamic Commercial Banks in Indonesia are among the banks that developed this product which was later called the Future Package (PMD). PMD is financing intended for women entrepreneurs or prospective entrepreneurs who belong to the poor group without collateral. In addition to providing financing, PMD also provides training to improve knowledge and entrepreneurial skills as well as monitoring debtor businesses. The purpose of this study is to be able to understand the marketing communication model that has been applied by Islamic banks to female customers, the majority of whom do not have financial literacy and are poorly educated so that they are interested in joining PMD products. The research method used is qualitative research with a case study approach. Then it produces the fact on the ground that Sharia Banks in marketing PMD products for women's empowerment are with an offline and online marketing mix. Product promotion tactics include events and experiences that include a variety of marketing communication tools.